On the new soliton and optical wave structures to some nonlinear evlouation equations - Bulut, Hasan; Sulaiman, Tukur Abdulkadir; Baskonus, Haci Mehmet (Springer Heidelberg, 2017)
In this study, with the aid of the Wolfram Mathematica software, the powerful sine-Gordon expansion method is utilized to search for the solutions to some important nonlinear mathematical models arising in nonlinear sciences, namely, the (2 + 1)-dimensional Zakharov-Kuznetsov modified equal width equations, the cubic Boussinesq equation and the modified regularized long wave equation. We successfully obtain some new soliton, singular soliton, singular periodic waves and kink-type solutions with complex hyperbolic structures to these equations. We also present the two- and three-dimensional shapes of all the solutions obtained in this study. We further give the physical meaning of all the obtained solutions. We compare our results with the existing results with the existing results in the literature.
Keywords: Zakharov-Kuznetsov Equation; Explicit